Continuous Use and Extended Use of E-Government Portals in Malaysia. Issue 15 (18th November 2021) - Yap, Ching Seng; Ahmad, Rizal; Newaz, Farhana Tahmida; Mason, Cordelia
ABSTRACT: This study aims to investigate the level of user satisfaction with the services provided by E-Government portals and to examine the influence of perceived value and virtual community engagement on citizens' satisfaction and their continuous and extended use intentions. Primary data are collected from a convenience sample of 1, 000 E-Government portal users via a questionnaire survey. The findings show that citizens are generally satisfied with the services provided by E-Government portals and have positive continuous use and extended use intentions. Both perceived value and virtual community engagement relate positively with citizen satisfaction, with the former has a relatively stronger influence. Citizen satisfaction also leads to continuous and extended use intentions. The findings shed lights on dimensions of E-Government portals that citizens considered valuable and the importance of virtual community engagement in influencing their satisfaction and subsequent use intentions.